If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 96 + -1p = 63 Solving 96 + -1p = 63 Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '-96' to each side of the equation. 96 + -96 + -1p = 63 + -96 Combine like terms: 96 + -96 = 0 0 + -1p = 63 + -96 -1p = 63 + -96 Combine like terms: 63 + -96 = -33 -1p = -33 Divide each side by '-1'. p = 33 Simplifying p = 33
| (9k^2)-9k+2=0 | | 26t+5a-4t-2= | | r-28=33 | | 84-v=29 | | (7z^2)-10z+3=0 | | 71-x=22 | | 8x-5=2x+11 | | 47=c-31 | | X^2+10x-11x=0 | | w/-6=-9 | | a-16=12 | | 45=79-h | | 7c+3=17 | | 45=54-d | | 47=54-d | | (8Z^2)+14z+5=0 | | 62=81-r | | 12i+7r-14i= | | 12i+7r-14y= | | 3t+1=7t | | 6a^2-13a+15=6a | | 95-b=73 | | 0=2x^2-20+50 | | f-25=25 | | 19t+5-17t=23 | | 1/10s= | | v-39=22 | | 28=35-a | | 4x^2=484 | | 3*1/5 | | 7x-y+8x+5y= | | 480ms= |